Effects of native, triglyceride-enriched, and oxidatively modified LDL on plasminogen activator inhibitor-1 expression in human endothelial cells. - Allison, B; Nilsson, L; Karpe, F; Hamsten, A; Eriksson, P (1999)
Whereas VLDL has consistently been shown to induce a concentration-dependent increase in the expression of plasminogen activator inhibitor-1 (PAI-1) in human umbilical vein endothelial cells (HUVECs) and liver cells, variable effects have been reported for native and oxidatively modified LDL. In the present study, activation of PAI-1 protein and mRNA expression by native LDL (nLDL), UV-oxidized LDL (uvLDL), and triglyceride (TG)-enriched LDL was studied in HUVECs by using different incubation times and a wide range of lipoprotein concentrations. No significant increase of PAI-1 protein expression was observed after 4 hours of incubation with nLDL or uvLDL. However, PAI-1 protein secretion from HUVECs was markedly enhanced after 18 hours of incubation with uvLDL (200% increase at 10 microg/mL). Stimulation of PAI-1 protein expression in HUVECs by nLDL was seen, however, after increasing the TG content of the LDL particle. LDL enriched in phospholipid had no effect on PAI-1 secretion. PAI-1 mRNA levels on northern blot increased in parallel with the activation of PAI-1 protein expression by native and modified forms of LDL. Low concentrations of TG-enriched LDL (10 microg/mL) and higher concentrations of nLDL and uvLDL (100 microg/mL) were found to increase the binding of a VLDL-inducible transcription factor to the PAI-1 promoter. These results indicate that the TG content of the LDL particle influences PAI-1 expression in endothelial cells. Low concentrations of uvLDL enhanced PAI-1 protein and mRNA expression in the HUVECs after an 18-hour incubation but did not influence the VLDL-inducible transcription factor. This suggests that low levels of oxidized LDL increase PAI-1 expression by a different mechanism than VLDL and TG-enriched LDL.